IMPLEMENTASI KERJASAMA FINANSIAL TEKNOLOGI ANTARA INDONESIA DAN SINGAPURA TAHUN 2017 - Sugiarto "; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to explain the implementation of cooperation between Indonesia and Singapore in the field of Financial Technology. The ollaboration between Indonesia and Singapore in the field of Fintech has been planned for 2017 and has only been realized since October 2018 in Bali. The signing of the memorandum of understanding (MoU), namely a memorandum of mutual understanding, was carried out by the chairman of OJK, Wimboh Wantoso, and the chairman of MAS, Ravi Menon. This agreement also facilitates access to investment, social, technology and education. Indonesia is one of the countries with the largest internet users in the world. The collaboration between Indonesia and Singapore is the first step to maximizing and improving the quality of technology, as well as increasing investment in financial technology in both countries. Data collection techniques are collected from various sources such as books, journals, official documents, and websites related to financial technology. The author uses the level of analysis of the nation state. This study uses the perspective of liberalism and international cooperation theory. Using this theory will explain how the implementation of the agreement that was signed by Indonesia and Singapore. The results of this study indicate that the implementation of cooperation between Indonesia and Singapore in the field of financial technology has increased the capacity of the digital economy and human resources in Indonesia, the high interest in fintech, the establishment of special schools teaching financial technology under the auspices of the Nongsa Digital Park, increasing Singapore's investment in Indonesia and implementation of the Regulatory and box program to review the feasibility of new companies entering Indonesia. keywords: digital economy, international cooperation, Nongsa Digital Park, financial technology. regulatory sandbox